From Myth to History and from History to Myth: Representations of Pípila, Popular Hero of the Mexican Independence Process (Palimpsesto, 2021)
The present work analyzes the complex historical position of the Pípila, hero of the Mexican independence. It will be argued that he is a subject in permanent transit between denial and recognition, which acquires the characteristics of a political myth. It seeks to explore the long-running tension between empirical data and imagination about the founding past of national identity, observing the mythical hypotexts that give meaning to the popular hero in a heterogeneous set of representations. His presence will be seen in historical narrations of the 19th and 20th centuries, and in various visual works of the 20th and 21st centuries: comic book, sculpture, mural and illustration.
Keywords: : Pípila; Mexican Independence; political myth; mythical hypotext